Use of inhibitors of the renin‐angiotensin system in hypertensive patients and COVID‐19 severity: A systematic review and meta‐analysis - Barochiner, Jessica; Martínez, Rocío (Journal of clinical pharmacy and therapeutics, 2020)
What is known and Objective Controversy has arisen in the scientific community on whether the use of renin‐angiotensin system (RAS) inhibitors in the context of COVID‐19 would be beneficial or harmful. A meta‐analysis of eligible studies comparing the occurrence of severe and fatal COVID‐19 in infected hypertensive patients who were under treatment with angiotensin‐converting enzyme inhibitors (ACEI) or angiotensin receptor blockers (ARB) vs no treatment or other antihypertensives was conducted. Methods PubMed, Google Scholar, the Cochrane Library, medRxiv and bioRxiv were searched for relevant studies. Fixed‐effects models or random‐effects models were used depending on the heterogeneity between estimates. Results and discussion A total of eighteen studies with 17 311 patients were included. The use of RAS inhibitors was associated with a significant 16% decreased risk of the composite outcome (death, admission to intensive care unit, mechanical ventilation requirement or progression to severe or critical pneumonia): RR: 0.84 (95% CI: 0.73‐0.95), P = .007, I2 = 65%. What is new and conclusion The results of this pooled analysis suggest that the use of ACEI/ARB does not worsen the prognosis of COVID‐19, and could even be protective in hypertensive subjects. Hypertensive patients should continue these drugs even if they become infected with SARS‐CoV‐2. Controversy exists on whether RAS inhibitors are beneficial or harmful in COVID‐19. In this meta‐analysis, the use of RAS inhibitors was not associated with a worse COVID‐19 prognosis and was even protective in hypertensive patients. Patients should continue these drugs during their COVID‐19 illness.